First-line lesional aspiration in acute stroke thrombectomy using a novel intermediate catheter: Initial experiences with the SOFIA. Issue 3 (June 2016) - Kabbasch, C; Möhlenbruch, M; Stampfl, S; Mpotsaris, A; Behme, D; Liebig, T
Introduction: Five randomized controlled trials (RCTs) on endovascular therapy (EVT) of stroke have proven a clinical benefit over conservative treatment or IV-thrombolysis alone. Lesional clot aspiration with a dedicated system can achieve revascularization without an additional retriever (a direct-aspiration first-pass technique, ADAPT), and the SOFIA has been shown to be both safe and efficacious in a multicentric retrospective study. We have evaluated a subset of these data acquired in two major stroke centers with regard to using the SOFIA for first-line lesional aspiration. Methods: Thirty patients with large-vessel occlusions treated with first-line lesional aspiration were identified. Procedural data, clot length, reperfusion success (mTICI), procedural timings, complications, and clinical status at admission, discharge and at 90 days were analyzed. Results: The median baseline NIHSS was 16. IV thrombolysis was administered in 15/30 patients. Ninety-three percent of occlusions were in the anterior circulation. TICI ≥ 2b was achieved in 90% of multimodality treatments; lesional aspiration was successful in 67% within a median time of 20 minutes. The highest first-attempt success rate was in MCA occlusions (median time to recanalization 10 minutes). There were no device-related events. Symptomatic intracerebral hemorrhage (sICH) occurred in 10%, but never with sole lesional aspiration. Embolization to new territories was recorded in 1/30 (3%). Median discharge NIHSS was 7; 30% were mRS ≤ 2 at discharge and 43% at 90-day follow-up. Conclusions: Lesional aspiration with SOFIA is in line with published data. The SOFIA may be used as a first-line device, aiming at fast recanalization by sole aspiration with good safety and efficacy. If unsuccessful, it converts into part of a stent retriever-based multimodality treatment.